Expression by Role-Playing: Teaching Offering and Giving Assistance - Fatoni, Akhmad Feri; Suprayitno, Emdat; Mark, Elladdadi; Xavier, Embrechts; Barroso, Uwe (Sekolah Tinggi Agama Islam Al-Hikmah Pariangan Batusangkar, West Sumatra, Indonesia., 2023)
The use of giving and offering help is the primary expression in communication. These expressions in English are often needed, especially for nursing, where meeting with the public, including foreigners, is possible. This study aimed to determine the process of providing material about the expressions used in giving and offering assistance to patients in English and how to pronounce the vocabulary using the role-play method. In this study, the researcher used a descriptive qualitative approach to the subject of nursing students in the first semester at Universitas Wiraraja. The result stated that giving and offering help with role-play occurred with several obstacles. The students' limited knowledge about expressions to provide and assist patients made the learning process not optimal. Only a few expressions were used to describe the expression giving and offering help. Some students had difficulty in choosing words, especially related to health-based words. Errors in pronouncing some vocabulary were also an obstacle in the learning, especially in expressing giving and offering some helps. In addition, due to the mispronunciation, the students speak with low fluency.